The Effectiveness of Acupressure Therapy on Dysmenorrhea Among Female Adolescents at SMPN 5 Jagoi Babang West Kalimantan 2025 - Lusiana; Putri Azzahroh; Bunga Tiara Carolin (Rajaki of Tulip Medika Publisher, 2026)
Background: Adolescence is a transitional period from childhood to adulthood characterized by physical, psychological, and social changes, including the biological functioning of the reproductive organs. Menstrual pain that is not promptly managed can affect an individual’s mental and physical functioning, thus requiring immediate intervention through pharmacological or non-pharmacological therapies. Acupressure therapy can be used as a treatment for dysmenorrhea by applying massage techniques to specific meridian points on the body. One of the points that can be used to relieve dysmenorrhea is the Hegu (LI4) point. Purpose: This study aimed to determine the effectiveness of acupressure therapy on dysmenorrhea among adolescent girls at SMPN 5 Jagoi Babang. Methods: This study employed a quasi-experimental design with a pretet-posttest two-group design approach. The sample consisted of adolescent girls selected using a total sampling technique. The participants were divided into two groups: the control group received no intervention, while the experimental group received acupressure therapy at the LI4 point. The paired t test was used for within-group analysis, and the independen t test was used for between-group analysis. Results: The results showed that acupressure therapy was effective in reducing dysmenorrhea among adolescent girls (p < 0.000). The administration of LI4 acupressure therapy was more effective than no intervention (p = 0.000). Conclusion: Acupressure therapy at the LI4 point is clinically effective and statistically significant in reducing dysmenorrhea compared to no intervention. Keywords: Adolescents, LI4 (Hegu) Acupressure, Dysmenorrhea